The Searchers - John Ford; Jeffrey Hunter; John Qualen; Natalie Wood; Olive Carey; Vera Miles; Ward Bond; John Wayne (USA C.V. Whitney Pictures, 1956)
When Ethan decide to go find the Indians who killed his family, he is joined by his nephew, Martin Pawley. The problem is that Pawley is half-Indian, and there's nothing in the world tha Edwards hate more than Indians. The journey to find the Indians and Edwards niece (and Pawley half-sister) last for years.
As a Civil War veteran spends years searching for a young niece captured by Indians, his motivation becomes increasingly questionable.
Alan Le May
Language(s): English
Subtitle(s): English, Turkish, German, Spanish, Dutch, Swedish, Norwegian, Italian
Keywords: Drama; Western